Molecular detection and characterization of Ehrlichia ruminantium from cattle in Mozambique - Matos, Carlos António [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; de Souza Ramos, Inalda Angélica [UNESP]; Mendes, Natalia Serra [UNESP]; Zanatto, Diego Carlos Souza [UNESP]; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP] (Elsevier, 2019)
Heartwater caused by Ehrlichia ruminantiumis a disease of domestic and wild ruminants and one of the most economically important tick-borne diseases in Africa. The present study aimed to investigate the occurrence and genetic diversity of E. ruminantium in blood samples from 210 cattle sampled in five districts of Maputo Province, Mozambique. DNA blood samples were initially submitted to PCR assays targeting E. ruminantium pCS20 gene fragments. Additionally, in order to assess the genetic diversity of E. ruminantium, the positive samples were submitted to a PCR assay targeting the E. ruminantium map1 gene. Finally, the amplicons were sequenced and phylogenetic position was inferred using the Maximum Likelihood method. PCR results revealed that the overall prevalence in Maputo Province was 15% of the animals sampled. E. ruminantium map1 sequences showed not to be conserved. In the phylogenetic analysis, E. ruminantium map1 genotypes were positioned into multiple-clades. This study provides information on the prevalence and genetic diversity of E. ruminantium in five localities of Maputo Province. The future immune control strategies against local E. ruminantium must be designed in the light of the genetic diversity of this parasite.
Keywords: Heartwater (cowdriosis); map1; Maputo Province; Mozambique; PCR; pCS20